Sistem Pengurusan Keselamatan dan Kesihatan Pekerjaan (OSHAH:18001) Analisis Kepada Penerimaan Faedah Pelaksanaannya Kepada Organisasi Di Malaysia - Arifin, Kadir; Aiyub, Kadaruddin; Awang, Azhar; Razman, Muhamad Rizal (Journal of Techno-Social, 2009)
Occupation Healthy and Safety Management (OSHAH) is one of the tool that can be use in voluntary way by the organization to overcome workers safety problems in the work place. For that reason, this paper work is done to see how the effects of OSHAH 18001:1999 implementation from the perspective of the benefits received by organizations which applied it in their organization. These are 26 organization from various sector are been given OSHAH 18001:1999 certification from SIRIM Qas Berhad and all that organization have been chosen to be respondent from this research. The analysis data method in this research have been done by using several test such as comparison test ( T test ), related test (khi-square test), relation (pearson correlation test) between primary variable and secondary variable. Beside that, this research is using the significant level off 90% (p=0.009 until p= 0.10) and 95% (p=0.01 until p= 0.05) to justify the result of comparison data. Research result shows that there is a significant benefit for the organizations that have been implement OSHAH 18001:1999 such as reduce the accident risk, increase employer awareness and thought and establish awareness among the workers.